FOOD NUTRITION TEST FOR FULLDAY CLASS STUDENTS THROUGH LESSON STUDY At MTs MUHAMMADIYAH BATANG - Susi Indria Wijayanti (Universitas Muhammadiyah Semarang, 2021)
Nutrients are needed by the body of living things, including humans. Humans need nutrition as a source of energy to survive. Among the nutrients needed by humans as a source of energy are carbohydrate and fat. To prove the content of carbohydrate and fat, it is necessary to nutritional test with the aim of providing experience for students to find out the nutritional content of the food they consume every day, especially carbohydrate and fat. The Food Nutrition Test is carried out using a qualitative descriptive method with the objects are bread, potato, carrot, cucumber, corn, butter, coconut milk, cheese and candlenut. Carbohydrate testing is by dripping Betadine and fat test by lubricating food to opaque paper. The subjects of this Food Nutrition Test are the students of MTs Muhammadiyah Batang Fullday School. Concept lesson study is applied in this activity. The results of nutrition test shows the foods that is consumed by students of MTs Muhammadiyah Batang Fullday School everyday which contain carbohydrates are rice, potatoes, corn and cassava. Foods that contain carbohydrates when dropped with betadine will change blue-black. As for foods which contain fat, they are applied with opaque paper, they will indicate the oil marks on the paper. These foods include butter, cheese, coconut milk and candlenut.Keywords: lesson study, carbohydrate and fat nutrition test